Pola Konsep Strategi Industrialisasi dan Perusahaan di Kabupaten dan Kota - Sintya Amilia Fernanda; Ahmad Fatih Fairuz Z; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research analyses effective industrialisation strategies in districts and cities, by assessing success factors and the role of firms. Regional industrialisation supports economic growth and job creation. Key factors influencing success include the quality of human resources, infrastructure, government policies and technology. Cluster approaches based on local potential and industrial estate development have proven effective. Companies play an important role in creating industrial ecosystems and running CSR programmes. Collaboration between the government, companies and communities is key to successful regional industrialisation.